Reflected backward stochastic differential equation driven by G-Brownian motion with an upper obstacle - Hanwu Li; Shige Peng (Bielefeld University, Center for Mathematical Economics (IMW), 2020)
In this paper, we study the reflected backward stochastic differential equation driven by G-Brownian motion (reflected G-BSDE for short) with an upper obstacle. The existence is proved by approximation via penalization. By using a variant comparison theorem, we show that the solution we constructed is the largest one.
urn:nbn:de:0070-pub-30049173
Keywords: 330; G-expectation; reflected backward SDEs; upper obstacle